Antecedents and consequences of brand experience in virtual sports brand communities: A value co-creation perspective - Zhuo, Jin-Yuan; Su, Rong-Hai; Yang, Hsi-Hsun; Hsu, Mao-Chou (Frontiers in Psychology, 2022)
The influence mechanism for brand experience in virtual sports brand communities is the subject of many studies but these do not feature a holistic consideration of antecedents and consequences, and the moderating role of brand attachment is unclear. Drawing on value co-creation theory, this study determines the impact of brand experience and its mechanism using data from 508 virtual sports brand communities. The results of the empirical tests show that value co-creation (i.e., corporate-initiated value co-creation and customer-initiated value co-creation) has a positive effect on brand experience and that brand experience has a positive effect on purchase intention. Brand attachment does not have a moderating role between brand experience and purchase intention so as the degree of brand attachment increases, brand experience does not increase purchase intention through brand attachment. This study determines the antecedents and consequences of brand experience in virtual sports brand communities from a value co-creation perspective, to determine the impact and mechanisms of virtual sports brand communities to guide the marketing practices of virtual sports brand communities.